PENGARUH ZAT PENGATUR TUMBUH 2,4-D (2,4-DICHLOROPHENOXYACETIC ACID) DAN KINETIN (6-FURFURYLAMINOPURINE) UNTUK PERTUMBUHAN TUNAS EKSPLAN PUCUK TANAMAN JABON (ANTHOCEPHALUS CADAMBA MIQ. EX ROXB.) SECARA IN VITRO - KARTIKA SARI, PENI (LenteraBio: Berkala Ilmiah Biologi, 2013)
Jabon (Anthocephalus cadamba Miq. Ex Roxb.) is one of Indonesia local plants that could potentially be developed for the improvement of the forest is in addition to the other purposes, such as reforestation, reclamation of mined lands. Production and productivity is relatively low due Jabon hard to get the seeds for cultivation techniques are traditionally performed. One way of propagation that can meet the demand of large amounts of seed and uniform growth is a tissue culture system. The purpose of this study is to determine the combination of 2,4-D concentration and the optimal kinetin produced shoots shoots jabon explants. Data were analyzed using one-way Anova to determine the effect of a given treatment, if there is a noticeable difference then will proceed to test Dual Duncan distance. The results showed that the treatment was able to induce MS+1.10-1 mg/L 2,4 D+3.10-1 mg/L kinetin shoots in 2 days the best optimal shoots high by 1.28 cm.